COMPARATIVE ANALYSIS OF ONLINE AND TRADITIONAL CLASSROOM LEARNING. (Scientific journal of the Fergana State University, 2025)
The rise of the online learning modality has transformed the educational landscape, providing flexibility and convenience, but calls into question its efficacy when compared to the more traditional form of physical interaction with students. This article investigates to address this gap by juxtaposing these internalization strategies with the help of relevant theories, empirical data and important findings. The paper examines the cognitive, constructivist and socio-cultural approaches in order to highlight the strengths and weaknesses of online and classroom teaching. Finally, the article integrates the findings of several studies to reflect the relationship between particular approaches used and the students’ academic performance and involvement in the learning process.